Nel solco della controstoria: società, governo e ordine nel pensiero amministrativo imperiale britannico - Cazzola, Matilde (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
This essay reconsiders British imperial administrative thought through the lens of Domenico Losurdo’s «counter-history of liberalism». The liberal reflection of a select number of British colonial governors and administrators is analysed around three major imperial crises: the American Revolution, the abolition of slavery in the West Indies, and the Indian Rebellion of 1857. By adopting a global perspective on these processes, the essay shows how the administrators of the British Empire contributed to the debates around some key notions of the modern liberal lexicon (empire, liberty, equality, citizenship, sovereignty, civilization) in a way that linked the United States independence to the French and the Haitian Revolutions, the emancipation of the West Indian enslaved to the work discipline of British labourers, and the constitutional developments in the colonies to the electoral reforms extending the franchise to the middle and the working classes in 19th-century Britain. The article especially focuses on the categories of government and order as the core concepts for a history of imperial administrative thought. Midway between theory and praxis, at the junction of state and society, and traveling from the metropole to the colonies (and back), British imperial administrators combined their speculation upon politics and society with the concrete implementation of governmental and legal techniques aimed to produce social and international order. Counter-history of liberalism; British Empire; administration; Global History; Government; Order.